Human rights and sexuality: transgender in the municipality of Arapiraca - Alagoas / Direitos humanos e sexualidade: transgêneros no município de Arapiraca - Alagoas - José Ferreira Leandro; Lívia de Oliveira Silva; Alana Carla Berto Santos; Rebecca de Oliveira Brito (); Swan Rocha Siqueira Tavares Abreu; João Vitor Calixto Rocha (Universidade Estadual de Alagoas, 2016)
The work in question relates the social context of transgender, as well as social relations. Thus, the objective of this work was to know the experience, how they view the gender change, the prejudice and the conquered rights of transgenders in the municipality of Arapiraca - Alagoas. The interest in developing such a project arose in order to understand how transgenders are living in a society considered conservative, despite the processes of social development, with all the principles protected by the Federal Constitution of 1988. For the accomplishment of the research was used interview, With about six transgenders residing in the municipality of Arapiraca, Alagoas. It was observed that there were many difficulties in the areas: social, cultural, legal and health